The Development of Photosystem II-Herbicide Detection Method Using Microalgae as a Biosensor - Desa, Shakinaz (1997)

(untitled)
Herbicides have been found to be significant pollutants of water bodies. In order to control and monitor the pollution, a convenient, sensitive and reliable method is needed. The main objective of this study is to develop a new method to measure the fluorescence yield of microalgae in order to detect photosystem II (PSII) specific herbicides in polluted water. The system was based on a simple mixing of microalgae with PSII specific herbicides. The measured signal was in the form of fluorescence intensity. The study involved the screening of test organisms, determining the best condition of the culture and obtaining a standard curve for each of the PSII herbicides. Only three herbicides were studied; atrazine, simazine and diuron. Chlorella vulgaris was found as the most suitable test organism compared with Chlorococcum sp., Scenedesmus quadriqauda and Selenastrum sp .. Nutrient replacement culturing method was selected as the best condition to grow C. vulgaris. A standard curve was determined for each of the herbicides. C. vulgaris was able to signal atrazine's concentration above 0.04µM according to the standard curve equation. Simazine can be signalled at above 0.05µM from its equation, while diuron can be signalled at above than O.09µM. However, -this basic study needs more infonnation and improvement to be done in the future, so that its full potential can be realised.